PENGARUH CORPORATE SOCIAL RESPONBILITY TERHADAP NILAI PERUSAHAAN DAN MANAJEMEN RESIKO BANK SYARIAH INDONESIA - Nur Fitria, Ika Ainun; Rahmatika, Arivatu Ni'mati (Universitas KH. A. Wahab Hasbullah, 2023)
The purpose of this research is to find out how Corporate Social Responsibility influences. The analysis results show that corporate social responsibility has a significant positive effect on company value. This means that the better the company implements CSR, the more the company value will increase. This research chooses a qualitative method with a descriptive approach to research the implementation of risk management in Islamic banks and Corporate Social Responsibility, therefore researchers must go directly to the field to explore problems related to the implementation of risk management in BSI and the influence of CSR on company value. This research is direct research on customers who save at BSI. Keywords: Risk management, Influence of CSR